Epithelial cell polarity and tumorigenesis: new perspectives for cancer detection and treatment - Coradini Danila; Casarsa Claudia; Oriana Saro (Acta Pharmacologica Sinica, 2016)
Loss of cell-cell adhesion and cell polarity is commonly observed in tumors of epithelial origin and correlates with their invasion into adjacent tissues and formation of metastases. Growing evidence indicates that loss of cell polarity and cell-cell adhesion may also be important in early stage of cancer. In first part of this review, we delineate the current understanding of the mechanisms that establish and maintain the polarity of epithelial tissues and discuss the involvement of cell polarity and apical junctional complex components in tumor pathogenesis. In the second part we address the clinical significance of cell polarity and junctional complex components in cancer diagnosis and prognosis. Finally, we explore their potential use as therapeutic targets in the treatment of cancer.